Sosialisasi Dan Pendampingan Pembuatan Nib Pada Sektor Kerajinan di Gamplong - Rizqi Kurnia Putra; Rochmad Bayu Utomo (Pusat Riset dan Inovasi Nasional, 2023)
There are still 50 percent of MSMEs in the craft sector in Gamplong who do not have a Business Identification Number (NIB) because they think that this document is trivial and do not understand how to obtain it. This service program aims to increase understanding of NIB and assist in the process of making NIB in the craft sector. The method used in this program is the presentation of material regarding NIB as well as assistance in making NIB door to door to MSMEs. The high level of enthusiasm of MSME players in this service program resulted in an understanding of NIB and NIB legality documents. We hope that this program can improve the economy of MSMEs, as well as help MSMEs gain access to capital.